Pengembangan Modul Ajar Biologi Kelas XI Berbasis Project Based Learning (PjBL) Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Sarwati, Sarwati; Indra Himayatul Asri; Titin Yuliana; Nur Annisa Fitri Badaruddin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to: (1) Develop a biology teaching module based on Project-Based Learning (PjBL) to enhance students' creative thinking skills. (2) Determine the feasibility and idealness of the (PjBL) based biology teaching module in enhancing students' creative thinking. (3) Assess the effectiveness of the (PjBL) based teaching module in improving students' creative thinking. This developmental research follows the Borg and Gall model, consisting of seven stages: initial information gathering, planning, initial product development, limited-scale testing, product revision, large-scale testing, and product revision. The subjects of this study included subject matter experts, biology teachers, design experts, 15 students for limited-scale testing, and 70 students for large-scale testing at SMAN 1 Pringgasela. Data collection techniques involved the used of questionnaires, and the data were analyzed using descriptive quantitative analysis. Based on the data analysis and discussion, it can be concluded that the (PjBL) based biology teaching module is feasible, ideal, and effective for use in the learning process. The feasibility was demonstrated by an average feasibility percentage of 84.52% from subject matter experts, and 86.07% from design experts. These ratings fall under the very feasible and feasible criteria. The idealness of the module was reflected in the average idealness scores of 3,72 from biology teachers and 2,94 from students, categorized as very ideal and ideal. The effectiveness of the teaching module was seen in the average N-Gain score, with the experimental class at 0.62 and the control class at 0.28 on a larger scale. The N-Gain scores suggest moderate effectiveness, categorized as reasonably effective. The average percentage of Project-Based Learning (PjBL) worksheets per group indicated that the worksheets were in the very creative category for enhancing students' creative thinking skills.